2001
DOI: 10.1081/ncn-100108321
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Base-Deuterated 2?-Deoxyadenosine Nucleosides and Their Site-Specific Incorporation Into Dna

Abstract: We report a four-step synthesis of 2 0 -deoxy-2-deuteroadenosine from 2 0 -deoxyadenosine in 38% overall yield. The more accessible 2 0 -deoxy-8-deuteroadenosine was also prepared and incorporated into DNA by automated solid phase synthesis (80% deuterium) using N 6 -benzoyl-2 0 -deoxy-8-deuteroadenosine-3 0 -O-(2-cyanoethyl-N,N-diisopropylphosphoramidite) in combination with acetyl-protected deoxycytidine and phenoxyacetyl-protected purine phosphoramidites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The results demonstrated that the replacement of protonated methanol with its deuterated analog within the same concentration of 2 H 2 O in the growth media slightly decreased the growth characteristics (Table 1, (Table 1, experiment 1). In the intermediate experiments (2)(3)(4)(5)(6)(7)(8)(9)(10), these parameters varied proportionally to the 2 Н 2 О concentration ( Table 1). The observed effect consisted in the increase in the lag-phase period and cell generation time with a simultaneous decrease in microbial biomass outputs on media with increasing 2 Н 2 О-content.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that the replacement of protonated methanol with its deuterated analog within the same concentration of 2 H 2 O in the growth media slightly decreased the growth characteristics (Table 1, (Table 1, experiment 1). In the intermediate experiments (2)(3)(4)(5)(6)(7)(8)(9)(10), these parameters varied proportionally to the 2 Н 2 О concentration ( Table 1). The observed effect consisted in the increase in the lag-phase period and cell generation time with a simultaneous decrease in microbial biomass outputs on media with increasing 2 Н 2 О-content.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we used a stepwise increasing gradient of 2 H 2 O-concentration in M9 growth media (from 24,5; 49,0; 73,5 up to 98% (v/v) 2 Н 2 О) in the presence of 2% (v/v) methanol and its 2 H-labeled analog ([ 2 H]methanol), because we assumed that gradual cell adaptation to 2 Н 2 О would have a favorable effect on the growth parameters of the strain. (2)(3)(4)(5)(6)(7)(8)(9)(10), these parameters varied proportionally to the 2 Н 2 О concentration ( Table 1). The observed effect consisted in the increase in the lag-phase period and cell generation time with a simultaneous decrease in microbial biomass outputs on media with increasing 2 Н 2 О-content.…”
Section: Resultsmentioning
confidence: 99%
“…The recent advance in technical and computing capabilities of these analytical methods has allowed a considerable increase the efficiency of carrying out biological studies with 2 H-labeled molecules de novo, as well as to carry out the analysis of the structure and function of nucleosides and their analogs at the molecular level [7]. In particular, 2 H-labeled ribonucleosides and their analogs are used in template-directed syntheses of deuterated RNA macromolecules for studying their spatial structure and conformational changes [8]. Perdeuteration and selective deuteration techniquemay be useful approaches for simplification of NMR spectra and for other structural studies of large biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the replacement of protonated methanol with its deuterated analog within the same concentration of 2 H 2 O in the growth media slightly decreased the growth characteristics (Table 1, (Table 1, experiment 1). In the intermediate experiments (2)(3)(4)(5)(6)(7)(8)(9)(10), these parameters varied proportionally to the 2 Н 2 О concentration ( Table 1). The observed effect consisted in the increase in the lag-phase period and cell generation time with a simultaneous decrease in microbial biomass outputs on media with increasing 2 Н 2 О-content.…”
Section: Preparation Of Deutero-biomass Of B Methylicum Vkpm B-3157mentioning
confidence: 99%